Diet of Odorrana chapaensis (Bourret, 1937) from Son La Province, Vietnam - Anh, Pham Van; Truong, Nguyen Quang; Hoang, Nguyen Van (Academia Journal of Biology, 2019)
Since there is currently a lack of data on the natural history and feeding ecology of Odorrana chapaensis, which was listed in the IUCN Red List (2019), we herein provided the feeding ecology of this amphibian species is virtually lacking. We herein provide data about the diet of O. chapaensis based on the results of our field work in Ngoc Chien Commune, Muong La District and Xim Vang Commune, Bac Yen District, Son La Province, Vietnam. We used the stomach-flushing method to obtain the stomach contents of 85 individuals at two survey sites. A total of 20 prey categories with 334 items, comprising 299 items of invertebrates and 35 unidentified items, were found in the stomachs of O. chapaensis. The dominant prey items of O. chapaensis were Araneae, Polydesmida, insect larvae, Blattodea, Coleoptera, Dermaptera, Lepidoptera, Hymenoptera, and Orthoptera. The importance index for these categories ranged from 3.5% to 32.5%. Coleoptera was the category with the highest frequency of prey items; its representatives were found in 45 stomaches.